Induction of labour at Jos University teaching, hospital, Jos, Nigeria: a four year review - Oyebode, Tinuade A.; Toma, Bose O.; Shambe, Iornum H.; Kahansim, Markswal L.; Embu, Henry Y.; Daru, Patrick H.; Sagay, Atiene S. (International Journal of Research in Medical Sciences, 2017)
Background: Induction of labour (IOL) is a common procedure that remains a relevant Obstetric procedure. The maternal and perinatal outcomes are paramount hence the need to review the intervention in order to implement needed change. Objectives: To determine incidence, indications, outcome and complications of induction of labour at the Jos University Teaching Hospital (JUTH), Jos, Nigeria. Methods: This was a retrospective study reviewing 584 women who had IOL in JUTH from January 2004 to December 2007. Parameters selected for review include parity, gestation age, outcome and cervical state prior to IOL. Results: Four hundred and eighty women had vaginal deliveries (82.2%). There were fifty two induced on account of antepartum Intra Uterine Foetal Deaths (IUFD), while 1.5% of the deliveries ended up as still births, 10.5% had birth asphyxia and neonatology review and care. Thirty two patients had various complications after IOL. There were no maternal mortalities. Conclusion: Parity and presence of IUFD were found to influence the outcome of IOL.